Exploring the managerial challenges of implementing a budget spending plan in the Department of Correctional Services in Gauteng region - Mohapi, Ralikhaoana Isaac (University of the Witwatersrand, Johannesburg, 2024)
The main purpose of this study was to explore the managerial challenges of implementing a budget spending plan in the Department of Correctional Services (DCS) in Gauteng. This study adopted an exploratory qualitative research design and used a semi-structured questionnaire to collect data from Financial and Non-Financial Managers. The study found no appropriate framework for the budget spending plan for the past three financial years (2020/21, 2021/22, and 2022/22). Non-financial Managers are not adequately trained in budget management and are not directly involved in budget preparation. The study also revealed that the DCSs’ leadership failed to implement an internal control measure to monitor procurement and contract management to prevent audit findings for not recurring in the past three financial years. The study also concludes that Financial Managers have never complied with policies and regulations during fund shifting to avoid overspending and underspending. The study recommends that the DCSs’ leadership regularly review the procurement process and budget according to policies and regulations. It also recommends that Financial Managers prioritise adequate funding for the Self-Sufficiency and Sustainability (SSS) projects to avoid sourcing items externally. Lastly, the study recommends that a comparable or similar study be conducted to research more on budget spending plans in other government departments nationally.
A research report submitted in fulfillment of the requirements for the Master of Management (in the field of Governance and Management), In the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Accountability; Budget Spending Plan; In-Year Monitoring; and Budget Constraints; SDG-8: Decent work and economic growth